Find f(x) and g(x) such that h(x) = (f @ g)(x)

h(x) = (6 - 8x)^2

Suppose that g(x) = 6 - 8x

f(x) = ?

Find f(x) and g(x) such that h(x) = (f @ g)(x)

h(x) = (6 - 8x)^2

Suppose that g(x) = 6 - 8x

f(x) = ?

Tutors, please sign in to answer this question.

New York, NY

Hi Keith,

We know h(x) = (6-8x)^2.

Also h(x) = (f@g)(x) and g(x)=6-8x.

So for the composite function f@g(x), we can replace g(x) by 6-8x,so we get

h(x)

since the question wants you to find f(x), we can simply replace 6-8x by x.

so from (1), we get

f(x) = x^2

Middletown, CT

Hi Keith;

g(x)=(6-8x)

f(x)=?

(f@g)x=h(x)=(6-8x)(6-8x)=(6-8x)^{2}

- Algebra 5692
- Algebra 1 4474
- Math Help 6138
- Algebra 2 3811
- Algebra Word Problem 2808
- Math 11930
- Math Help For College 1528
- Algebra Equation 326
- Algebra Question 259
- College Algebra 1390